Maternal and fetal outcomes in pregnancy beyond 40 weeks of gestation: an observational study - Sirsam, Shyamkumar S.; Jawir, Gayatri M.; Patil, Bhupendra V.; Wahane, Aparna; Padole, Mrunal S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pregnancy beyond 40 weeks, or postdated pregnancy, is associated with increased maternal and perinatal morbidity. The present study aimed to evaluate maternal and fetal outcomes in pregnancies extending beyond 40 weeks of gestation. Methods: This prospective observational study was conducted among 200 pregnant women with gestational age >40 weeks admitted to the department of obstetrics and gynaecology, government medical college and hospital, Akola, Maharashtra. Data were collected regarding maternal demographics, mode of delivery, onset of labor, complications, and neonatal outcomes. Statistical analysis was performed using descriptive methods. Results: The mean maternal age was 26.7±3.2 years, with 64.5% being primigravida. Sixty percent of women delivered at term (40-40+6 weeks), 30% at late term (41-41+6 weeks), and 10% beyond 42 weeks. Vaginal delivery occurred in 63.3% and caesarean section in 36.7% of cases. Labor induction was required in 45%, predominantly using prostaglandins. Maternal complications included oligohydramnios (25%), prolonged labor (20.5%), and postpartum hemorrhage (19%). Fetal complications included fetal distress (29%) and meconium-stained liquor (23%). NICU admission was needed in 18% of neonates, mainly for respiratory distress, hypoglycemia, and perinatal asphyxia. Most neonates (81.6%) had normal birth weight (2.5-3.9 kg), with 12.2% macrosomic. Conclusions: While most postdated pregnancies had favourable outcomes, maternal and neonatal risks increased with advancing gestation. Early identification, timely induction, and vigilant intrapartum monitoring are essential to optimize outcomes in pregnancies beyond 40 weeks.